2010
DOI: 10.2527/jas.2009-2409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ractopamine and sex on serum metabolites and skeletal muscle gene expression in finishing steers and heifers

Abstract: We evaluated growth-related responses to ractopamine in steers and heifers. Sixteen Angus steers (512 kg) and 16 Angus heifers (473 kg) housed in individual pens were used in a complete block design. At 90 to 97 d before the experiment, steers were implanted with 120 mg of trenbolone acetate and 24 mg of estradiol-17beta (Component TE-S) and heifers were implanted with 140 mg of trenbolone acetate and 14 mg of estradiol-17beta (Component TE-H). Treatments were arranged as a 2 x 2 factorial and included sex (st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…Also, Macías-Cruz et al (2010) observed greater yield of ribs, hindquarter and legs, but lower yield of forequarter, neck and shoulder in ewe lambs fed ZH during a warm season. It should be mentioned that there is no precise explanation for our results obtained, as previous studies in beef cattle have reported that ZH improved the development of type II muscle fibre, and consequently, muscle growth (Mersmann 1998;Walker et al 2010). Based on the above, we expected a greater yield of some wholesale cuts, mainly in those cuts with high amount of type II muscle fibre (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Also, Macías-Cruz et al (2010) observed greater yield of ribs, hindquarter and legs, but lower yield of forequarter, neck and shoulder in ewe lambs fed ZH during a warm season. It should be mentioned that there is no precise explanation for our results obtained, as previous studies in beef cattle have reported that ZH improved the development of type II muscle fibre, and consequently, muscle growth (Mersmann 1998;Walker et al 2010). Based on the above, we expected a greater yield of some wholesale cuts, mainly in those cuts with high amount of type II muscle fibre (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Conversely, this experiment reported that wholesale cut yields were not affected by addition of ZH in the finishing diet of ewe lambs. Previous studies indicated that the effects of ZH on wholesale cuts depend on the presence and amount of type II muscle fibers located in each cut, given that β2-adrenergic receptors are mainly located in these fibers (Mersmann, 1998;Walker et al, 2010). However, the reason for the lack of ZH effects herein on cuts with high abundance of type II muscle fiber (legs, shoulders, and loin) is unclear.…”
Section: Zilpaterol Hydrochloridementioning
confidence: 97%
“…According to Walker et al (2010), steers, when compared to heifers, had a tendency to have higher levels of β2-adrenergic receptor mRNA in the LT compared to the…”
Section: The Influence Of Calpastatin Can Be Countered By Higher Calpmentioning
confidence: 99%